Analisis Empirik tentang Penganggaran Daerah dan Pandemi COVID-19 - Junita, Afrah; Meutia, Tuti; AS, Agus Putra; Nita Erika Ariani (Jurnal Penelitian Ekonomi Akuntansi, 2025)
This study aims to examine differences in budget size, budget changes, and budget absorption between the budget period before the Covid-19 pandemic (in 2018-2019) and during the Covid-19 pandemic (in 2020-2021) in district and city governments in Aceh Province. The sample in this study was 23 regencies/cities with the data used sourced from local government financial report documents that have been audited by external auditors and regional revenue and expenditure budgets that have been determined by regional regulations or qanuns. The results of the analysis show that there is a significant difference between the period before and during the Covid-19 pandemic for the amount of the budget and changes in the budget, while for budget absorption there is no difference. This may be due to Government intervention in budget policies during the Covid-19 pandemic. These results have implications for the need to redefine changes in regional budgets and affirm the authority of local governments in managing their finances within the framework of implementing consistent and effective fiscal decentralization.